Low anterior resection syndrome (LARS) after sphincter-sparing rectal cancer surgery. Incidence and risk factors - DALKILIÇ, MUHAMMED SAİD; AKIN, MUHAMMED İKBAL; YEGEN, ŞEVKET CUMHUR (My University, 2022)
© 2022, Edizioni Luigi Pozzi. All rights reserved.BACKGROUNDS: Low anterior resection syndrome (LARS) was defined with symptoms such as frequency, incontinence, urgency, and constipation in patients who underwent Sphincter-Sparing Rectum Surgery (SSRC). In this study, LARS rates and risk factors of the patients who underwent SSRC were Investigated. MATERIAL METHOD:The medical records of patients with SSRC at general surgery department were examined retrospectively. Clinical characteristics, neo/adjuvant chemo-radiotherapies, distal resection levels, open/laparoscopic procedures, postoperative complications, and pathological outcomes were recorded. LARS scoring system defined by Emmertsen and Laurberg was used to calculate LARS scores. RESULTS: The number of eligible patients was 129. The rectal resection was performed by either low anterior resection (LAR) or very low anterior resection (VLAR). VLAR was used to specify that had anastomosis <5cm to the anal verge. The median follow-up time was 12 (1-30) months. LARS were detected in 60 (%47) patients. LARS rates were significantly higher in the patients underwent VLAR (n: 35 9% vs. 48%<0,001). In univariate analysis, the level of distal resection, open surgeries, neoadjuvant RT, and diversion with temporary stoma were significantly different in LARS group. However, in multivariate analysis, distal resection level was the only significant risk factor for LARS. CONCLUSION: Low anterior resection syndrome (LARS) was frequently seen in patients who underwent sphincter-sparing rectum surgery (SSRS). It was detected that distal resection levels were the most important risk factor for the development of LARS. This result showed that LARS should not be disregarded in patients underwent SSRS. Y.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Bowel Disfunction; Cancer; Incontinence; LARS; Rectum